Conceptualization and assessment of family caregivers` anticipatory grief in palliative care - Coelho, Alexandra (2021)
Introduction: In cancer end-of-life trajectory, the family caregiver (FC) faces the patient´s successive functional losses and the perspective of imminent death, thus giving rise to a grief response that precedes the actual loss. Despite being emotionally painful, the experience of Anticipatory Grief (AG) was thought to be protective against the impact of sudden death. The AG concept is particularly useful in palliative care, as it allows for preventive intervention, by preparing FC for the terminally ill patient´s inevitable death. However, due to the lack of conceptual clarity, contradictory empirical results have been found, challenging the previous idea that AG was associated with stress reduction afterwards. Instead, it was proposed that the cumulative effect of the caregiver's distress exacerbates the grief reaction, thus predicting worse adjustment to loss. Recent research conceived pre-death grief manifestations as part of a continuum of grief symptoms that, in some cases, tends to persist over time, leading to Prolonged Grief Disorder (PGD). Although this perspective meets the purpose of early detection of those individuals at risk of developing PGD, on the other hand it fails to capture the multidimensionality and specificity of the AG concept. Overall, the AG phenomenology has been little explored in cancer FC, so there are not yet known its specific characteristics, nor the dynamics underlying individual differences in emotional response to this experience. Besides, the existing assessment instruments are self-reported, so they cannot grasp the implicit meanings that FC attribute to their experience. For clinical purposes, it is important to develop empirically based criteria that guide health professionals in a comprehensive evaluation of FC´s support needs. Accordingly, this research aims to contribute to a more comprehensive view and measurement of palliative care cancer family caregiver´s grief experience by analysing the trajectory of grief symptoms, their determinants and multidimensionality of anticipatory grief concept. As general objectives, we established: (a) To describe the trajectory of PGD symptoms and their determinants in a sample of the Portuguese sample of cancer FC followed in palliative care; (b) To contribute to the conceptualization and operationalization of the family caregiver anticipatory grief phenomenology by developing a clinical assessment instrument to measure individual differences in anticipatory grieving process. Methods: This research project encompasses a literature review, followed by a series of multilevel studies, employing quantitative, qualitative and mixed method approaches. First, a literature review was conducted for gaining perspective on this problematic and capture the main domains of the AG concept. Then, a survey instrument design, including two longitudinal studies, addressed the first main objective (Empirical studies I and V). Data was collected from a convenience sample of cancer FC accompanied in a palliative care (PC) out-patient consultation. At the beginning of accompaniment (T1), the participants were evaluated through self-reported measures on the following variables: demographics, perception of illness, involvement in caregiving, caregiver burden, coping mechanisms, quality of the relationship, mental health symptoms and pre-death prolonged grief symptoms. During bereavement (T2, 6 - 12 months after the patient´s death), participants were contacted by phone to evaluate PGD symptoms. The initial phase of collection and analysis of results (Empirical study I, n= 94) consisted in the validation of the PG-12, a brief self-report diagnostic tool adapted from the Prolonged Grief Disorder Questionnaire to evaluate the presence of pre-death PGD. In a second phase, this sample was enlarged to perform a multivariate analysis of PGD predictors, both pre and post-death (Empirical study V, n= 156 at T1; n= 87 at T2). The other part of this research, corresponding to the second main objective, relied in qualitative and mixed method analysis. Two original cross-sectional and one longitudinal study were conducted using sub-samples of participants selected from the previous works. Data from interviews were submitted to thematic analysis (Empirical study II, n= 26) and then cross tab analysis with self-reported results for identifying patterns of AG according to the pre-death manifestations intensity (Empirical study III, n= 72). In this analysis, we used a combined inductive and deductive analysis, applying concepts from attachment theory to classify the FC´s response patterns. Findings from the qualitative studies were refined and operationalized into structured criteria, giving rise to a new assessment tool for evaluating individual differences in dealing with AG experience. Results: Results showed that PG-12 is a valid and reliable unidimensional diagnostic tool, with predictive value for post-death PGD symptoms. In a sample of cancer FC in palliative care, up to 38.6% presented PGD symptomatology, with tendency to decrease during bereavement, although in many cases, severe manifestations persisted for longer. These findings provide evidence for both the perspectives of stress reduction and cumulative stress, which turned out to be complementary in explaining the diversity of the caregivers’ grief manifestations evolution. In addition to intrapersonal (e.g., coping mechanisms) and relational factors (e.g., proximity of the relationship with the patient at the time of illness), the psychological distress and burden related to end-of-life caregiving contributed significantly to explain PLP variations, suggesting that FC´s grief manifestations cannot be decontextualized from the experience of end-of-life caregiving. Accordingly, two main dimensions emerged from qualitative data: (i) traumatic distress of witnessing the significant other´s life-threatening conditions, (ii) relational distress, inherent to the end-of-life caregiving relationship and future separation. Each theme includes several categories, conceived as different challenges that require a constant effort of emotional regulation. AG was therefore defined as the FC´s response to the perceived menace to the other´s life and subsequent anticipation of loss, in the context of an end-of-life caregiving relationship. Individual differences were classified according to self-reported pre-death grief intensity, resulting in the configuration of anticipatory grieving patterns, described qualitatively in the light of attachment theory: (i) avoidant (ii) adjusted, (iii) intense, and (iv) traumatic. Indicators were operationalized into evaluation criteria, constituting a new manualized instrument – the Family Caregivers´ Anticipatory Grief Clinical Interview (FcAG-CI). In this preliminary phase of validation, it has shown acceptable values of validity and reliability. The dimensionality of AG construct was confirmed, as well as the latent structure with four groups. Individual differences were found to be predictive of pre-death mental health outcomes. This association was not found with bereavement adjustment, which suggests that despite the continuity of PGD symptoms, the experience of AG is qualitatively different from post-death grief. However, it is also possible that this result is due to differences in the quantitative and qualitative assessment modalities and/or limitations of the study in terms of the follow-up sample size. Conclusion: This research project contributes to the literature in several ways. First, by providing a comprehensive and parsimonious definition of AG, we contribute to a more precise and self-differentiated understanding of this phenomenon. Second, by integrating qualitative data from semi-structured in-depth interviews with theoretical concepts, we developed a conceptual model for explaining individual differences in AG. Third, on operationalizing empirically based assessment criteria, we created a new manualized instrument to guide clinical evaluation and distinguish anticipatory grieving patterns. Fourth, by collecting prospective data, we contribute to the description of the determinants and outcomes of this experience in long term. Specifically in the Portuguese reality, where the investigation is still scarce, it is important to generate valid empirical data that inform about the actual impact of end-of-life caregiving. In sum, results from this research contribute to a more coherent and elaborated understanding of AG, with clear clinical implications in terms of measurement, intervention and education of health professionals towards a more sensitive and effective response to family caregivers´ needs.